Improvement of Inter-Professional Collaborative Work Abilities in Mexican Medical and Nursing Students: A Longitudinal Study - Tuirán-Gutiérrez, Guillermo J.; San-Martín, Montserrat; Delgado-Bolton, Roberto; Bartolomé, Blanca; Vivanco, Luis (Frontiers in Psychology, 2019)
Background: Inter-professional and interpersonal relationships in collaborative work environments can prove to be critical elements in healthcare practice. When implementers fail to understand the importance of a collaborative perspective, this can lead to communication problems which ultimately harm the users. Objectives: To improve the inter-professional collaborative work skills of Mexican students in their first year of medical and nursing degrees through the use of a training program geared toward development of interpersonal skills and interdisciplinary work. Methods: The sample was composed of 162 students (62 males and 99 females) from the School of Healthcare Sciences of the Autonomous University of Coahuila, Mexico. The main measures used were the Jefferson Scale of Empathy (JSE); the Jefferson Scale of attitudes toward inter-professional collaborative work between medical and nursing professionals (JSAPNC); and the Jefferson Scale of lifelong learning (JeffSPLL). The entire sample was divided into two groups (experimental and control groups). Both groups attended an extra-curricular program using a coaching methodology. In the first case the topic focused on attitudes toward inter-professional collaborative work. In the second case, the program focused on addiction. Both programs ran for 4 months. Psychometric instruments were applied at the beginning and at the end of both programs. After analyzing the reliability of the instruments, an ANOVA test was performed. Results: The control group of medical students showed a deterioration in the development of collaborative work skills (p<0.01), whereas in the experimental group this deterioration was not present. In the experimental group of nursing students, a significant increase in the development of collaborative work skills (p<0.05) was observed. The differences were clearly due to the professional area of study (p<0.001). Conclusions: There are differences in collaborative work skill development among different professional areas. These differences can be reduced through the implementation of a program aimed at developing collaborative work and interpersonal skills in the early stages of training.